2020
DOI: 10.1002/oa.2854
|View full text |Cite
|
Sign up to set email alerts
|

Holocene Khoesan health: a biocultural analysis of cranial pathology and trauma

Abstract: A bioarchaeological assessment of human skeletons provides an objective opportunity to study and understand past peoples. Crania were analysed to evaluate health and well‐being of a past Khoesan sample in southern Africa. These data were analysed temporally and spatially (coastal vs inland), and by sex and age. Cranial and dental pathology of 150 adult individuals from the Human Skeletal Collection at the University of Cape Town were assessed. Most individuals were of coastal origin, equally distributed betwee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 66 publications
(90 reference statements)
1
8
0
Order By: Relevance
“…Additionally, the prevalence of cribra orbitalia reported in these modern populations were 24.3% (O'Donnell et al, 2020), 29.6% (Hens et al, 2019), and 33.3% (Rothschild et al, 2021), similar to prevalence reported in many populations across time and around the world (Bec ˇi c et al, 2014;Blom et al, 2005;Carlson et al, 1974;Gibbon & Davies, 2020;Juengst et al, 2017;Kalov a et al, 2017;Kozak & Krenz-Niedbała, 2002;Kyle et al, 2018;Lallo et al, 1977;Łubocka, 2000;Nathan et al, 1966;Novak, 2011;Okumura & Eggers, 2005;Redfern et al, 2015;Yaussy et al, 2016;Zhang et al, 2016).…”
Section: Critical Assessment Of the Pathological Etiology Of Cribra O...supporting
confidence: 75%
See 1 more Smart Citation
“…Additionally, the prevalence of cribra orbitalia reported in these modern populations were 24.3% (O'Donnell et al, 2020), 29.6% (Hens et al, 2019), and 33.3% (Rothschild et al, 2021), similar to prevalence reported in many populations across time and around the world (Bec ˇi c et al, 2014;Blom et al, 2005;Carlson et al, 1974;Gibbon & Davies, 2020;Juengst et al, 2017;Kalov a et al, 2017;Kozak & Krenz-Niedbała, 2002;Kyle et al, 2018;Lallo et al, 1977;Łubocka, 2000;Nathan et al, 1966;Novak, 2011;Okumura & Eggers, 2005;Redfern et al, 2015;Yaussy et al, 2016;Zhang et al, 2016).…”
Section: Critical Assessment Of the Pathological Etiology Of Cribra O...supporting
confidence: 75%
“…The prevalence among well‐documented samples from modern times appears similar to prevalence reported in many populations across time and around the world with wide‐ranging diets, lifestyle, disease risks, etc. For example, Gibbon and Davies (2020) document a cribra orbitalia prevalence of 23% in a Holocene Khoesian sample from southern Africa; Juengst et al (2017) documents prevalence of 33% from seven archeological sites in the Copacabana Peninsula at the Titcaca Basin that date from 800 BC – 200 AD; Zhang et al (2016) note a prevalence of 30.3% among a Late Shang population from Anyang, China; Bečić et al (2014) reports a prevalence of 21% among a seventh‐ninth century AD population from the Ostrovica‐Greblje graveyard in Croatia; Novak (2011) documents a prevalence of 35% from a late Medieval Cemetery from Koprivno in Southern Croatia; Blom et al (2005) documents prevalence of 23.1% from coastal populations of Peru dating from 200 BC–1,476 AD; Kozak and Krenz‐Niedbała (2002) report a prevalence of 27.6% in a Kołobrzeg, Poland population dating from the 14th–18th century AD; Łubocka (2000) documents a prevalence of 30.2% from Ostrów Lednicki, an island on the Lednica Lake—Wielkopolska Province, Poland from the 12th–14th centuries AD; Okumura and Eggers (2005) note a prevalence of 29.4% from Sambaqui Jabuticabeira II in Brazil dating from 2,890 ± 55–2,186 ± 60 BP; Lallo et al (1977) document a prevalence of 33.8% among a population from Dickson Mounds and Eiden in Illinois and Ohio (USA) dating from 900–1,350 AD (Dikson Mounds) and 1,490 ± 55 AD (Eiden); and Carlson et al (1974) documents a 21.4% prevalence from a Sudanese Nubia population dating from 350 BC–1,400 AD.…”
Section: Discussionmentioning
confidence: 99%
“…The skeletal material housed in these repositories is largely derived from archaeological sites of the Later Stone Age. The majority of the sample comes from the South African Cape region, spanning areas between the coast and the inland Cape Fold Mountain belt (Figure 1) (Gibbon & Davies, 2020). Most of the skeletons assessed had been radiocarbon dated, with the majority dating within the last 5,000 years.…”
Section: Methodsmentioning
confidence: 99%
“…South Africa has a diverse population requiring population‐specific sex estimation standards (Bidmos et al, 2010; Bidmos & Mazengenya, 2021; Dayal et al, 2022; Krüger et al, 2017; Mokoena et al, 2019; Robinson & Bidmos, 2011; Sallie et al, 2022; Vance et al, 2011). To date, population‐specific standards for archaeological San and Khoekhoe populations are lacking, although researchers have noted that application of global standards is unsatisfactory due to skeletal gracility, small stature, and active lifestyle (Gibbon & Davies, 2020; Ginter, 2008; Hausman, 1982; Kurki et al, 2012; Pfeiffer et al, 2019; Pfeiffer & Harrington, 2011). In this study, we use the term “San and/or Khoekhoe” (rather than “Khoisan”), as preferred by the National San Council of South Africa and representatives of descendant communities (Hitchcock et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Trauma analyses in bioarchaeology allow for exploration of the individual's lived experience and human behaviour in the past (Gibbon & Davies, 2020; Lovell, 1997). Trauma on the cranium is relatively reliable indicator of interpersonal violence and has been well studied (Galloway, 1999; Gibbon & Davies, 2020; Harrod, 2018; Judd & Redfern, 2012; Jurmain, 1991; Lovell, 1997; Martin & Akins, 2001; Martin & Harrod, 2015; Osterholtz, 2012, 2013; Stirland, 1996; Tung, 2007, 2012). Moderate and severe cranial traumas lead to traumatic brain injury (TBI), which is described as a nondegenerative, noncongenital insult to the brain from an external mechanical force (Roozenbeek, Maas, & Menon, 2013).…”
Section: Introductionmentioning
confidence: 99%